NF‐κB Has a Direct Role in Inhibiting Bmp‐ and Wnt‐Induced Matrix Protein Expression. (6th August 2015) - Tarapore, Rohinton S; Lim, Jason; Tian, Chen; Pacios, Sandra; Xiao, Wenmei; Reid, Daniel; Guan, Hancheng; Mattos, Marcelo; Yu, Bo; Wang, Cun‐Yu; Graves, Dana T
ABSTRACT: The host response to pathogens through nuclear factor κB (NF‐κB) is an essential defense mechanism for eukaryotic organisms. NF‐κB‐mediated host responses inhibit bone and other connective tissue synthesis and are thought to affect the transcription of matrix proteins through multiple indirect pathways. We demonstrate that inhibiting NF‐κB in osteoblasts increases osteocalcin expression in vivo in mice with periodontal disease. Mutating NF‐κB binding sites on osteocalcin (OC) or bone sialoprotein (Bsp) promoters rescues the negative impact of NF‐κB on their transcription and that NF‐κB can inhibit Wnt‐ and Bmp‐induced OC and Bsp transcription, even when protein synthesis is inhibited, indicating a direct effect of NF‐κB. This inhibition depends on p65‐p50 NF‐κB heterodimer formation and deacetylation by HDAC1 but is not affected by the noncanonical NF‐κB pathway. Moreover, NF‐κB reduces Runx2 and β‐catenin binding to OC/Bsp promoters independently of their nuclear localization. Thus, inflammatory signals stimulate the direct interaction of NF‐κB with response elements to inhibit binding of β‐catenin and Runx2 binding to nearby consensus sites and reduce expression of matrix proteins. This direct mechanism provides a new explanation for the rapid decrease in new bone formation after inflammation‐related NF‐κB activation. © 2015 American Society for Bone and Mineral Research.